A New one-pot three-component synthesis of 4-Aryl-6-cycloamino-1,3,5-triazin-2-amines under microwave irradiation - Muhammad Syafiq, S; Ahmad Junaid,; Tiekink, Edward R. T. *; Dolzhenko, Anton V (2021)
A new method for the fast synthesis of diverse 4-aryl-6-cycloamino-1,3,5-triazin-2-amines was developed. The synthesis is performed under microwave irradiation in a one-pot manner from cyanoguanidine, aromatic aldehydes, and cyclic amines. Their three-component reaction in the presence of hydrochloric acid produced dihydrotriazines, which were then converted (without isolation) to the targeted compounds via aromatic dehydrogenation in the presence of alkali. The reaction tolerated various aromatic aldehydes (including heterocyclic) and cyclic amines. Crystal structures of two representative 4-aryl-6-morpholino-1,3,5-triazin-2-amines were established by X-ray crystallography. The results of preliminary biological screening identified potent antileukemic activity for 6-(3,4-dihydroisoquinolin-2(1H)-yl)-4-phenyl-1,3,5-triazin-2-amine.